Consumption of meat and meat products among students of the University of Costa Rica - Chacón Villalobos, Alejandro (Población y Salud en Mesoamérica, 2021)
Objective: to establish and analyze patterns of consumption of meat and meat products in students of the University of Costa Rica. Methodology: a basic study of the profile of the university consumer was carried out using a survey with 499 students (268 women and 231 men, between 16 and 29 years old), evaluating age, biological sex, consumption habits, type of meat preferred and most consumed meat product, reasons for purchase and places where they buy. Chi square evaluations, factorial ANOVAS and descriptive statistical analysis were used as statistical tests. Results: poultry is the most consumed meat (96.5%), followed by beef (91.9%). The consumption of meat is a daily habit for 23.2% of the students, while 17.6% consumes it at least 3 times a week. Good taste (84% of the cases) is the main reason for consumption above the nutritional value (51.9%). A majority do not participate in the purchase of meat (52.7%), preferring those who do the supermarkets (45%). The perceived quality is the main criterion for selecting the product, as well as the confidence in the place where they buy. About 87.0% consume sausages regularly, being more usual a frequency of 1 to 2 times a week (49.8%). Wet cured ham (89,0%) and wieners (83,0%) were the most frequently consumed, with no commercial brand predilection in 49.5% of the cases. Conclusion: around 96.4% of the students regularly consume meat and derived products, being those who decline mainly vegans. No relationship of these practices with the age and sex was established.